(3LdjI GdaQSGf hTYGQ GdTLYGfs - (3Ydj Hf YHO GdQMef Hf gPjd GdaRGQj GdCfOdSj,J (B763 (3g` s ((3CMeO Hf CMeO Hf CMeO HQLS s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ef YdjfG HGdEjeGf hSNQ dfG GdCfYGe ai eMce GdbQBf s
(3BNQgG (B:s
(3hGfTQ HQjM GdfVQ YPHGJ GdZHWI dOjg GfJgi HMeO Gddg hJhajbg s
(3HChdgG agQSJ ddeNWhWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B121s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs